Traditional massage “Peuseul” for pregnant women in Kuta Village and its impact on pregnant women's well-being: A qualitative study - Ningrum, Widya Maya; Purnamasari, Kurniati Devi; Fatimah, Siti (Interdisciplinary International Journal of Conservation and Culture, 2024)
“Peusuel” is a traditional massage practice performed on pregnant women in Tatar Sunda, believed to have various benefits for maternal and fetal health. This study aims to explore how Peusuel is implemented, understand the experiences of pregnant women who undergo Peusuel, and evaluate its impact on their physical and emotional well-being. The observed variables include physical discomfort levels (such as back pain, swelling, and fatigue), emotional states (including anxiety and mood changes), and social connectedness. The key parameters measured were frequency and duration of the Peusuel sessions and the involvement of community members in the process. Using qualitative research methods, particularly in-depth interviews and participant observations, data were collected from pregnant women who have experienced Peusuel, as well as from traditional practitioners and family members involved. Data were analyzed through thematic analysis to identify recurring patterns and insights. This analysis revealed that Peusuel not only helps reduce physical discomfort during pregnancy but also contributes to emotional relief by alleviating anxiety and stress. Additionally, it strengthens social and cultural ties between pregnant women and their communities, creating a sense of belonging and support. This study provides important insights into the preservation and development of the traditional practice of Peusuel in the context of modern health, while also highlighting its potential integration as a complementary approach in maternal care.